2010
DOI: 10.1016/j.neuropsychologia.2009.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Errors recruit both cognitive and emotional monitoring systems: Simultaneous intracranial recordings in the dorsal anterior cingulate gyrus and amygdala combined with fMRI

Abstract: We studied error monitoring in a human patient with unique implantation of depth electrodes in both the left dorsal cingulate gyrus and medial temporal lobe prior to surgery. The patient performed a speeded go/nogo task and made a substantial number of commission errors (false alarms). As predicted, intracranial Local Field Potentials (iLFPs) in dorsal anterior cingulate indexed the detection of errors, showing an early differential activity around motor execution for false alarms, relative to correct response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
84
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 119 publications
(91 citation statements)
references
References 78 publications
7
84
0
Order By: Relevance
“…Extensive details regarding the stimuli, task parameters and RT calibration procedure used in this experiment can be found in Vocat et al (2008) and Pourtois et al (2010).…”
Section: Stimuli and Taskmentioning
confidence: 99%
See 2 more Smart Citations
“…Extensive details regarding the stimuli, task parameters and RT calibration procedure used in this experiment can be found in Vocat et al (2008) and Pourtois et al (2010).…”
Section: Stimuli and Taskmentioning
confidence: 99%
“…The ERN component is a negative brain potential with a fronto-central scalp distribution (maximum amplitude at FCZ electrode position), peaking early following the onset of erroneous motor responses (typically in a window spanning from 0 until 100 ms after incorrect key presses). The neural generators of the ERN have been consistently localized in the dorsal Anterior Cingulate Cortex across several studies (dACC, see Dehaene, Posner, & Tucker, 1994;Bush, Luu, & Posner, 2000;Debener et al, 2005;van Veen & Carter, 2006;Pizzagalli, Peccoralo, Davidson, & Cohen, 2006;Ridderinkhof, Nieuwenhuis, & Braver, 2007;Vocat, Pourtois, & Vuilleumier, 2008;Pourtois et al, 2010). Time-frequency analyses showed that the ERN was primarily driven by transiently phase-locked theta-band power increase to the subject's motor response (Luu, Tucker, & Makeig, 2004).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The CC is implicated in a diverse array of functions, such as emotion (George et al., 1995; Kross, Davidson, Weber, & Ochsner, 2009; Liotti et al., 2000; Rogers et al., 2004; Rolls, Grabenhorst, & Parris, 2008; Walter et al., 2008, 2009), movement (Beckmann, Johansen‐Berg, & Rushworth, 2009; Paus, 2001; Picard & Strick, 1996, 2001), self‐relevant assessment (Kelley et al., 2002; Vogt, Vogt, & Laureys, 2006), cognition (Luo et al., 2007; Pourtois et al., 2010; Sohn, Albert, Jung, Carter, & Anderson, 2007; Ursu, Clark, Aizenstein, Stenger, & Carter, 2009), memory (Maguire, 2001), visuospatial orientation (Vogt et al., 2006), navigation, imagination, and planning for the future (Vann, Aggleton, & Maguire, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Source localization results point to the dorsal anterior cingulate cortex (dACC) as the main generator of both ERN (Dehaene et al, 1994;Yeung et al, 2004;van Veen and Carter, 2006) and FRN (Miltner et al, 1997), and the implication of the dorsal ACC in error detection (and correction) has been confirmed with various neuroimaging techniques, including functional magnetic resonance imaging (fMRI, e.g., Holroyd et al, 2004;Debener et al, 2005), magnetoencephalography (MEG, e.g., Miltner et al, 2003;Keil et al, 2010), and intracranial recordings (Niki and Watanabe, 1979;Brazdil et al, 2002;Halgren et al, 2002;Brazdil et al, 2005;Wang et al, 2005;Emeric et al, 2008;Pourtois et al, 2010).…”
Section: Introductionmentioning
confidence: 99%